The Influence of ESG and NIM on Company Value by Company Size: Pengaruh ESG dan NIM Terhadap Nilai Perusahaan dengan Ukuran Perusahaan - Sari, Mei Shovi Nurlita; Naruli, Akhmad; Magdalena, Fitria (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Firm value reflects investor perception of performance and prospects, while banking stability is closely linked to financial and sustainability practices. Specific Background: Environmental, Social, and Governance (ESG) disclosure and Net Interest Margin (NIM) are considered key indicators in assessing sustainability and financial performance in the banking sector. Knowledge Gap: Prior studies show inconsistent findings on ESG–firm value relationships, with limited focus on banking using NIM and the moderating role of firm size over a long observation period. Aims: This study analyzes the relationship between ESG disclosure and NIM on firm value, with firm size as a moderating variable in Indonesian listed banks during 2013–2024. Results: The findings reveal that ESG disclosure and NIM simultaneously relate to firm value with limited contribution, ESG shows a negative relationship, NIM is not significant, and firm size does not moderate these relationships. Novelty: This study integrates ESG and NIM within the banking context using firm size moderation and a relatively long observation period. Implications: The results indicate that sustainability practices in Indonesian banking have not been fully valued by the market, highlighting the need to improve transparency and integration of sustainability with financial performance to strengthen investor confidence and firm value. Highlights• ESG disclosure shows a negative association with market valuation• Net interest margin does not relate significantly to market assessment• Company scale fails to strengthen sustainability and financial linkages KeywordsESG Disclosure; Net Interest Margin; Firm Value; Firm Size; Banking Sector